KEEFEKTIFAN MODEL DISCOVERY YANG DIKEMBANGAKN DENGAN BANTUAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN TEKS EKSPOSISI PADA PESERTA DIDIK KELAS X SMA NEGERI 1INDRAMAYU - Pandi Sudarsono; Abdul Rozak; Indro Nugroho (Jurnal Inovasi Penelitian, 2021)
The latest curriculum in 2013 which began to be applied in high school / vocational school in Indonesian language logic also caused changes in the process and student learning outcomes so it is necessary to conduct research on the learning process of students with the 2013 curriculum in Indonesian subjects in class X high school. The objectives of this study are (1) to describe the implementation of Discovery learning model developed with the help of audio visual media in exposition text learning in Indonesian subjects in class X SMA, (2) Analyze the effectiveness of exposition text learning through the Discovery model developed with the help of audio visual media in grade X high school students, (3) Describe students' responses to the learning of the Discovery model developed with the help of audio visual in the learning of exposition text Indonesian subjects in class X high school. This research was a development research up to the third stage. The research subjects were taken with a purposive technique set as many as 61 people, namely 1 Indonesian language teacher, and 60 X grade students of SMA 1 Indramayu. Data collection techniques using questionnaires, tests (assessment), observation, and documentation. The data analysis technique used is descriptive analysis and mean different test. The results of this study concluded that (1) the implementation of learning through discovery models developed with audio visual media on exposition text material amounted to 92.5%. The assessment of devices in the discovery model developed with audio visual media media exposition text material in the RPP is valid with a percentage of 75% and 80.77% expert validation is valid, (2) learning devices in the discovery model developed with audio visual media media exposition text material is effective as evidenced by the difference in the average value of exposition writing works between the experimental and control classes where the average value of the experimental class writing works is higher than the control class, (3) students' responses to learning through the Discovery model developed with the help audio visual exposition text material Indonesian subjects in class X high school included in the excellent category.